(3QSGdI GdYTbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCdJ CjOc Gddg Cf CLYd dc QSGdI JJVef Gdbhd ai GdYTb Ydi SHjd GdEjLGR GdYTb ai cd hGMO ef GdghjGJ GdKGfi ai PcQ hLhg GdYTb s
(3BNQgG (B:s
(3aEPf GcKQ GdeWdb bO jYTb HMceJg Cf jfGd efg fjdkG hZPG HdZfG gPG GdeHdZ adfNJe GdQSGdI hGdMeO ddg hGgH GdbhI Ydi NJegG JeJ GdQSGdI GdYTbjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs